Comparison of 368 Patients Undergoing Surgery for Lumbar Degenerative Spondylolisthesis From the SPORT Trial With 955 From the NSQIP Database. Issue 5 (1st March 2015) - Golinvaux, Nicholas S.; Basques, Bryce A.; Bohl, Daniel D.; Yacob, Alem; Grauer, Jonathan N.
Abstract : Study Design: Retrospective cohort. Objective: To compare demographics and perioperative outcomes between the Spine Patient Outcomes Research Trial (SPORT) lumbar degenerative spondylolisthesis arm and a similar population from the National Surgical Quality Improvement Program (NSQIP) database. Summary of Background Data: SPORT is a well-known surgical trial that investigated the benefits of surgical versus nonsurgical treatment in patients with various lumbar pathologies. However, the external validity of SPORT demographics and outcomes has not been fully established. Methods: Surgical degenerative spondylolisthesis cases were identified from NSQIP between 2010 and 2012. This population was then compared with the SPORT degenerative spondylolisthesis study. These comparisons were based on published data from SPORT and included analyses of demographics, perioperative factors, and complications. Results: The 368 surgical patients with degenerative spondylolisthesis in SPORT were compared with 955 patients identified in NSQIP. Demographic comparisons were as follows: average age and race (no difference; P > 0.05 for each), sex (9.1% more female patients in SPORT; P = 0.002), smoking status (6.6% more smokers in NSQIP; P = 0.002), and average body mass index (1.1 kg/m 2 greater in NSQIP; P = 0.005). Larger differences were noted in what surgical procedure was performed ( P < 0.001), with the most notable difference being that the NSQIP population was much more likely to include interbody fusion than the SPORT population (52.4% vs. 12.5%). Most perioperative factors and complication rates were similar, including average operative time, wound infection, wound dehiscence, postoperative transfusion, and postoperative mortality (no differences; P > 0.05 for each). Average length of stay was shorter in NSQIP compared with SPORT (3.7 vs. 5.8 d; P = 0.042). Conclusion: Though important differences in the distribution of surgical procedures were identified, this study supports the greater generalizability of the surgical SPORT degenerative spondylolisthesis study based on similar demographics and perioperative outcomes when compared with patients from the NSQIP database. Level of Evidence: 3 Abstract : The degenerative spondylolisthesis arm of Spine Patient Outcomes Research Trial evaluated surgical or nonsurgical treatment of this condition. Demographics, perioperative factors, and complications were compared between Spine Patient Outcomes Research Trial and a national cohort from National Surgical Quality Improvement Program. Many comparisons between the groups were similar. The greatest difference was the significantly higher number of interbody fusions in National Surgical Quality Improvement Program.